Morphology and phylogeny reveal a new species of Corynespora from Xizang Autonomous Region, China - Zhao, Yun-Wei; He, Shu-Cheng; Hyde, Kevin D.; Zhao, Qi (Phytotaxa, 2025)
Corynespora bayiensis, a novel species isolated from decayed wood in Bayi County, Xizang, China, is distinguished by its scattered colonies exhibiting a coloration ranging from brown to black, and features mononematous, either straight or flexuous conidiophores with polytretic, terminal conidiogenous cells. The morphological characteristics matche with the generic concept of Corynespora. Phylogenetic analyses utilizing concatenated sequences of 28S rDNA, translation elongation factor 1-alpha (tef1) and internal transcribed spacer (ITS) sequences have substantiated that C. bayiensis represents a distinct monophyletic lineage within the genus. In light of the integrated morphological and phylogenetic data, we formally propose it as a new species of Corynespora. This study enhances the understanding of fungal diversity in the previously underexplored region of Xizang Province, China.